Multilevel level single phase inverter implementation for reduced harmonic contents - Taha Ahmed Hussein (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Selective harmonic elimination technique SHE is adopted in this work to reduce the harmonic contents in single phase cascaded multilevel inverter. The firing instants for the electronic switches MOSFETs in the inverter are calculated off line for five level to thirteen level inverter. An Arduino microcontroller is programmed to cope with different topologies of the multilevel inverter. The implemented multi-level (MLI) inverter results are compared with Simulink simulation program and are found very close to each other. SHE technique works at system frequency (50 Hz or 60 Hz) and the switching losses are very small. The sinusoidal pulse width modulation SPWM requires a carrier frequency not less 20 times the system frequency so SHE approach is found to be superior compared with SPWM. Also, SHE technique shows significant reduction in THD as the number of levels increased. Results for the output voltages and currents along with their frequency spectrum are shown and compared with traditional SPWM.